PHYSICOCHEMICAL CHARACTERIZATION AND STABILITY EVALUATION OF MEMBRANE-TYPE PATCH WITH CURCUMIN NANOEMULSION AS RESERVOIR - Fauzi Rahman; Fauzi Rahman; Ana Maria Ulfa (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Curcumin is a bioactive molecule derived from turmeric (Curcuma longa L.) that has pharmacological properties including antioxidant, anti-inflammatory, and anti-osteoarthritis actions. Howev er, curcumin has some limitations, including lower bioavailabi lity due to poor solubility and substantial first-pass metabolism. Curcumin can also be used in nanoemulsion systems. The nanoemulsion is combined with a membrane-type patch system to enhance and prolong curcumin's activity. The membrane-type patches were created using the solvent casting process with three different concentrations of HPMC as the polymer: F1 (6%), F2 (8%), and F3 (10%). The patches were evaluated for physicochemical parameters such as thickness, folding endurance, weight homogeneity, moisture content, pH, and active ingredient content, as well as stability using cycle tests. The results showed that different HPMC concentrations had a substantial effect on the patches' physicochemical properties. Higher HPMC concentrations resulted in increased folding endurance, weight, thickness, and active ingredient content, but moisture content and pH decreased. Stability tests revealed that the patches were stable in terms of folding endurance, weight homo geneity, & thickness, but unstable in terms of moisture content & pH